Encouraging Traditional Market through Customer Satisfaction - Udjianto, Didit Welly; Astuti, Rini Dwi; Hastuti, Sri Rahayu Budi; Muharam, Thala Nugra (RSF Conference Series: Business, Management and Social Sciences, 2021)
Progress of village development is very dependent on the financial independence of the village. Financial independence is reflected in the amount of original village income. One source of original village income comes from market retribution. Market retribution revenue will increase if the market can develop properly. Customer satisfaction is the key to the success of a market. This study analyzes consumer satisfaction at Kembangsari Market, Srimartani Village, Bantul Regency, and the factors that influence satisfaction using a logistic regression model. The results showed that the level of consumer satisfaction was 72.71 percent. Factors that influence consumer satisfaction are easy-to-market accessibility, good product quality, and guarantees provided. Infrastructure factors and the responsibility of traders have not been able to increase customer satisfaction.